Antidepressant Effects of a Persian Medicine Remedy on Multiple Sclerosis Patients: A Double-Blinded Randomized Clinical Trial: - Khalili, Mohammad; Adalat, Maryam; Ayromlou, Hormoz; Haririan, Sajjad; Fazljou, Seyyed Mohammad Bagher; Rezaeizadeh, Hossein; Safari, Ali Akbar; Zargaran, Arman (Galen Medical Journal, 2019)
Background: Multiple sclerosis (MS), an inflammatory neurodegenerative disease of the central nervous system, is accompanied by some psychiatric disorders, one prominent example of which is depression. The aim of this study was to investigate the effects of a Persian herbal medicine treatment that contains Crocus sativus, Hypericum perforatum, Cinnamon verum, and Vitis vinifera on fatigue and sleep disorders in MS patients. Materials and Methods: A Persian medicine remedy containing C.sativus, H.perforatum, C.verum, and V.vinifera was tested for its ability to improve the symptoms of depression in MS patients. This randomized double-blind clinical study was performed among 52 patients with MS who were allocated to their respective research groups through blocked randomization. The patients were treated for 4 weeks with either the drug or the placebo. To quantify the symptoms of depression, Beck depression inventory (BDI) was used. Results: Forty-six patients completed the study. In the course of the study, as the primary outcome, BDI decreased in the drug group (p=0.000) and the placebo group (p=0.001) significantly, but the rate of change in the drug group was significantly higher than in the placebo group (-13.9 Â± 8.6 vs. -3.9 Â± 4.3, p=0.000). While analyzing time and treatment effect for BDI, significant decreases in BDI were observed for the drug group, but not in the placebo group (p= 0.001). Conclusion: The present study suggests that Persian medicine remedy treatment in combination with chemical drugs may improve depression symptoms in MS patients. More investigations are needed to discover the exact mechanisms and processes involved. [GMJ.2019;8:e1212]